O Conselho Estadual dos Direitos da Criança e do Adolescente do Espírito Santo e sua relação com a Secretaria de Estado de Assistência Social e Direitos Humanos - Lang, Aline Elisa Maretto (2015)
The history of Brazilian social policies designed at children and adolescents indicates a past marked by the neglect of the government with this segment of the population. Only in 1990, after the promulgation of the Children and Adolescent Statute, this generational segment has been considered as citizens. The statute also established changes in the management of social policies. Among these changes, there is the institutionalization of the Councils for the Rights of Children and Adolescents, public agencies, parity, deliberative and responsible for the formulation of public policies designed to children and adolescents. This dissertation consists of a study of the State Council for the Rights of Children and Adolescents of the Espírito Santo, involving the last two administrations: 2011-2013 and 2013-2015. Aims to analyze the relationship of the State Council with the Secretary of State for Social Assistance and Human Rights, responsible for management of social assistance at the state level. As techniques for data collection were used the documentary research and semi-structured interviews with counselors and the Secretary servers. The data presented characterized the Council, its structure, organization and operation as well as the historical characteristics of the Secretary, their role in the management of social assistance and its structure. Data analysis was carried out considering the following aspects: the exchange of information between the Council and the Secretary, the actions realized in partnership, participation of Council in the formulation of plans and state policies, and the main debates and resolutions issued by the Council. The results indicate that although the Council is an important actor in the Rights Guarantee System and, due to that, a space of articulation between the different actors of this network, the development of their actions still occurs in a timely and isolation. In this way, we found a weak relationship between the Council and the Secretary. It has been a challenge for the different actors that are involved on this system develop actions together and defense of the rights of children and adolescents in Espírito Santo.